Care-full data, care-less systems: making sense of self-care technologies for mental health with humanistic practitioners in the United Kingdom - Spors, Velvet; Flintham, Martin; Brundell, Pat; Murphy, David (Frontiers in Computer Science, 2023)
The days of dusty couches in therapists' offices behind closed doors are long gone. Now, personalised mood tracking, therapy appointments and breathing exercises are just mere clicks (or taps) away: Technologies for self-care (SCTs) that focus on mental health are both a flourishing industry and an academic field of interest. As societal, and cultural artefacts, SCTs for mental health are imbued with values, worldviews, and assumptions about these concepts by their designers and developers. Here, current SCTs tend to lean towards a more medical(ised) approach due to being shaped by dominant views of mental health as an individualised issue.However, this approach is only one of many potential pedagogies and approaches. As an alternative, we explore what SCTs for mental health could be like, from a humanistic, personcentred standpoint: We conceptualise mental health in holistic terms, as an experiential quality of everyday life. To this end, we report on two engagements with humanistic practitioners and the person-centred approach as a guiding principle: First, we ran a workshop informed by the Rogerian "encounter group". This approach is focused on providing the space to meaningfully meet and relate to people. Inspired by this concept, we brought together humanistic practitioners to openly explore what technology for (self-)care means for them. Second, we build on the insights from the aforementioned study by organising an asynchronous, online whiteboard for humanistic practitioners-counsellors, students-in-training, therapists, and researchers-to explore their utopian, realistic and dystopian visions of SCTs. Through thematic analysis and affinity-clustering these engagements, we construct an understanding that technology within a person-centred, humanistic context is a constrained, ambiguous undertaking, yet also one full of potential. We conclude the paper by sketching out three design opportunities for how the person-centred approach, and humanistic psychology in general could be integrated into caring technologies.